WarGames [videorecording (DVD)] - Lasker, Lawrence; Parkes, Walter F.; Schneider, Harold; Badham, John, 1939-; Broderick, Matthew, 1962-; Coleman, Dabney, 1932-; Wood, John, 1930-2011; Sheedy, Ally (MGM Home Entertainment, 1998)
Young electronics wizard David Lightman unwittingly hooks into America's supersecret wargames computer and the world is suddenly threatened with nuclear annihilation.